Callus Induction from Stem Explants of Binahong (Anredera cordifolia (Ten.) Steenis) with the Addition of Picloram and BAP - Aulia, Siska Na'ilil; Habibah, Noor Aini (Al-Hayat: Journal of Biology and Applied Biology, 2024)
The many benefits of medicinal plants require development techniques that aim to produce high and diverse secondary metabolite contents. The purpose of this study was to analyze the effect of the concentration of picloram and BAP and determine the optimal concentration in inducing binahong callus. The research design used was a completely randomized design with two factors, namely the combination of picloram and BAP (0, 1, 2, and 3 ppm). The incubation process of binahong callus was carried out for 40 days after planting (DAP). The observed callus growth indicators consisted of days to callus formation (days), percentage of callus explants (%), callus morphology (texture and color), and callus diameter. Data on days to callus formation and frequency of callus explants were analyzed using the Kruskal-Wallis test and further tested by Dunn if there was a significant effect. The results showed that picloram significantly affected the parameters of days to callus formation and the percentage of callus explants, while BAP significantly affected the parameters of days to callus formation and did not significantly affect the percentage of callus explants parameter. At concentrations of 1 ppm, 2 ppm, and 3 ppm, picloram had a significant effect on both the days to callus formation and the percentage of callus explants parameters. BAP at concentrations of 1 ppm, 2 ppm, and 3 ppm only had a significant effect on the parameter of days to callus formation appearance and was not significant in the percentage of callus explants parameter. The interaction between BAP and picloram had a significant effect on the parameters of days to callus formation and the percentage of callus explants. The resulting callus has a compact texture with callus colors ranging from white, and green, to brown. The most optimal concentration in all indicators is 0 ppm BAP + 1 ppm picloram with days to callus formation of 6 DAP, 100% explants form callus, overall callus is white with compact texture, and has a very high callus growth.